Metatheses of Indonesian Segments in Malay Dialects - Fauzi Syamsuar (Linguistik Indonesia, 2026)
Metatheses are found in the cognates shared by the languages derived from the same ancestral language. A previous study recapitulated the cognates shared by Indonesian – a language code derived from a standard variation of Malay – and thirty-four Malay dialects in Indonesia. Abundant cognates with metatheses were found. However, no sufficient explanatory was reported dealing with the distribution of the metatheses. This article gives the explanatory. The data used in this analysis were selected from the previous study, i.e. the phonological forms of the cognates with metatheses. The analyzed metathesized-segments involve consonants, vowels, and segment-clusters. In comparison to vowels, consonants are more involved. The discussion of the metatheses is based on the syllabification-differences between the cognates. The patterns of metatheses comprise perceptual metatheses, reciprocal metatheses, metatheses with segment-insertions, metatheses with segment-deletions, and metatheses with segment-alternations. In addition, the metathesized of segment as the result of length-alternations are also found.